EFEKTIVITAS KETEPATAN SASARAN DALAM PENYALURAN PKH KELUARGA PETANI KELURAHAN MERAS KECAMATAN BUNAKEN KOTA MANADO - Rahasia Meyssel Anneke; Charles R. Ngangi; Leonardus R. Rengkung (AGRI-SOSIOEKONOMI, 2017)
This study aims to see the accuracy of the target in the distribution of Family Hope Program of farmers family of Meras village, Bunaken subdistrict, Manado City. The study was conductd from February to April 2017. Thye data used are primary data and second data. This research was conducted by direct interview technique with 11 (eleven) respondents. The result of this study indicate that the implementation of the distribution of PKH in the village of Meras has been runing well, beneficiaries perform the obligations as stipulated by the Departements of Social Affairs related to education and health. After PKH children are more diligent in school, in the field of hyealth has been running well children aged 0-6 years, pregnant women and postpartum women have the assurance of getting adequate nutrition thyrough examination, provision of vitamins, immunization and weight weighing routinely in health center that exist in Tongkaina.